ANALISIS KESALAHAN PENGGUNAAN EJAAN DALAM SURAT DINAS LEMBAGA PEMASYARAKATAN KELAS II-A PALU, SULAWESI TENGAH - M. Asri Bannu (Multilingual, 2016)
One of official communication devices is letter. The language applied in the letter need to be well arranged to gain its communication aim. The spelling system is one of the aspect that need to be arranged. This aspect becomes the problem in this research, how Indonesian spelling system is applied in the official letter of Lembaga Pemasyarakatan Kelas II-A, Palu, Sulawesi Tengah (Penitentiary Class II-A, Palu, Central of Sulawesi) in particular. The descriptive analytic is applied in this research. The source of data is the out-letter archives of the rehabilitation. Documentation technique is the technique of collecting data in this ressearch. According to the analysis of of 21 letters, there are ten common mistakes in apllied the spelling system. Those ten are (1) the mistake in using letters, (2) the mistakes in using preposition, (3) the mistake in using ordinal number, (4)the mistake in using words combination, (5)the mistake in using abbreviation and acronym, (6) the mistake in using adapted word, (7) the mistake in using full stop, (8) the mistake in using comma, (9) the mistake in using hyphen, and (10) the mistake in usingslash.